THE EFFECT OF BIOLOGY IN CONTEXT LEARNING ON STUDENT COGNITIVE LEARNING OUTCOME - Sabila, Husna; Dewahrani, Yulilina Retno; Miarsyah, Mieke (Faculty of Teaching and Education, University of Wiraraja, 2019)
Natural Science Education aims to help learners to be able to understand the natural surroundings include process, facts and principles that exist in nature. One of the aspects that support the success of understanding science and the process of learning science is the application of science literacy. The study was aimed to determine the effect of Biology in Context learning on cognitive learning outcome of junior high school student grade VIII in science subject. The research was conducted in Bekasi State Junior High School 2 at the first semester of the 2018/2019. The sampling technique used purposive sampling with a total sample 72 students obtained through the calculation of Slovin formula. The method used is the experimental method, non equivalent control group design. Data collection is done with the instruments of students cognitive learning outcomes. The analysis prerequisite test used is the normality test using Kolmogorov-Smirnov and the homogeneity test using Levene test. Hypothesis tested with the t test and the normalized gain value test. Based on the results of hypothesis test, there is the influence of Biology in context learning on the student cognitive learning outcome. Biology in context learning can improve student cognitive learning outcomes better than guided inquiry learning, which is equal to 66.4% or 0.45 in the calculation using normalized gain.